2006
DOI: 10.1542/peds.2005-2160
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Clinician Feedback to Improve Quality of Care for Inner-city Children With Asthma

Abstract: Patient-specific feedback to inner-city providers increased scheduled asthma visits, increased asthma visits in which medications were stepped up when clinically indicated, and reduced emergency department visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
99
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 35 publications
0
99
0
Order By: Relevance
“…37,96 Several studies included children. 5,37,46,85,96 Nine studies reported a reduction in ED visits or hospitalizations 5,[36][37][38]46,84,85,95,96 (5%-60%) among pre-post studies (all statistically significant) and 1% to 7% among the RCTs. 5,37,95 SOE: moderate.…”
Section: Clinical Pharmacy Supportmentioning
confidence: 97%
See 2 more Smart Citations
“…37,96 Several studies included children. 5,37,46,85,96 Nine studies reported a reduction in ED visits or hospitalizations 5,[36][37][38]46,84,85,95,96 (5%-60%) among pre-post studies (all statistically significant) and 1% to 7% among the RCTs. 5,37,95 SOE: moderate.…”
Section: Clinical Pharmacy Supportmentioning
confidence: 97%
“…94 95 supplemental feedback protocols, 5 and structured pathways/algorithms. 37,96 Several studies included children.…”
Section: Clinical Pharmacy Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Kattan et al described a program where clinical information, including medications use, was collected from patients and their families, and then provided to their primary care physician in conjunction with recommendations for medication changes. 18 This resulted in a significant increase in appropriate stepping up of asthma therapy (46% of visits) compared to a control group (35.6% of visits). Lee et al studied the impact of providing a review of individual patient medications in addition to educational material: although there was a drop in SABA use from 300 to 200 puffs per month, there was no change in clinical outcomes as measured by emergency visits and asthma related hospitalisation.…”
Section: Impact Of Strategies To Improve Prescribingmentioning
confidence: 99%
“…No difference between groups in airway hyperresponsiveness (p=0.09), improvement in nocturnal symptoms groups A and C No physician outcomes reported de Vries et al 18 Increase number of children with SABA prescriptions (p<0.01), fewer children on LABA with no ICS (p=0.03) (positive change)…”
mentioning
confidence: 98%